2022
DOI: 10.2166/nh.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of CMIP5 and CMIP6 in hydrological responses of the Yellow River Basin, China

Abstract: Investigation of the role of multiple general circulation model (GCM) ensembles in obtaining comprehensive knowledge of hydrological responses across the Yellow River Basin (YRB), China, is still of substantial importance. This study evaluates the performance of the Coupled Model Intercomparison Project Phase 6 (CMIP6) models in simulating the hydrological regime in the YRB and compares the results with those from CMIP 5 (CMIP5). The comparison is performed between 21 GCMs from CMIP6 under three Shared Socioec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…This study indicated that precipitation will increase faster in the next 30 years than in the past, and the rate of increase under the SSP245 scenario was projected to be higher than that under the RCP4.5 scenario (Figure 6). The above results have been validated by other studies (Guo et al, 2022; Li et al, 2021; Piao et al, 2021). In the Yellow River Basin, relative to the period of 1971–2000, there was a projected increase in precipitation of 3.45–4.70% and 6.77–15.40% during 2026–2055 and 2066–2095, respectively, in CMIP6.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study indicated that precipitation will increase faster in the next 30 years than in the past, and the rate of increase under the SSP245 scenario was projected to be higher than that under the RCP4.5 scenario (Figure 6). The above results have been validated by other studies (Guo et al, 2022; Li et al, 2021; Piao et al, 2021). In the Yellow River Basin, relative to the period of 1971–2000, there was a projected increase in precipitation of 3.45–4.70% and 6.77–15.40% during 2026–2055 and 2066–2095, respectively, in CMIP6.…”
Section: Discussionsupporting
confidence: 86%
“…In the Yellow River Basin, relative to the period of 1971–2000, there was a projected increase in precipitation of 3.45–4.70% and 6.77–15.40% during 2026–2055 and 2066–2095, respectively, in CMIP6. In comparison, for CMIP5 there was a projected increase of 2.58–2.96% and 3.83–9.95% during the same time periods (Guo et al, 2022). In southern South America and western North America, the rate of change in total precipitation for CMIP6 in the future under various scenarios was always greater than that for CMIP5 (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The YRB is situated in northern China (32°-42°N, 95°-120°E), and is approximately 1900 km long from east to west and 1100 km wide from north to south, with a basin area of 7.95×10 5 km² (Guo et al, 2022) (Fig. 1).…”
Section: Study Areamentioning
confidence: 99%
“…The YRB is situated in northern China (32 • -42 • N, 95 • -120 • E), and is approximately 1900 km long from east to west and 1100 km wide from north to south, with a basin area of 7.95 × 10 5 km 2 [19] (Figure 1). The area has a continental climate, vast territory and numerous mountain ranges.…”
Section: Study Areamentioning
confidence: 99%